2016
DOI: 10.1515/msp-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Site preference and electronic structure of Mn2RhZ (Z = Al, Ga, In, Si, Ge, Sn, Sb): a theoretical study

Abstract: The electronic structure and magnetism of Mn 2 RhZ (Z = Al, Ga, In, Si, Ge, Sn, Sb) Heusler alloys have been studied by using first-principles calculations. Three half-metallic ferromagnets, namely, Mn 2 RhAl, Mn 2 RhGe and Mn 2 RhSb have been considered. The calculated equilibrium lattice constant increases with increasing atomic number of Z atoms lying in same column of periodic table. The calculated total magnetic moments M tot are 2 µ B /f.u. for Mn 2 RhAl and Mn 2 RhGa, 3 µ B /f.u. for Mn 2 RhSi, Mn 2 RhG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It opens the doors for researchers involved in spintronics. The HAs are remarkable due to their active role in the spin‐injection devices, 13‐17 spintronic devices and high thermoelectric performance, 18‐20 tunnelling magneto‐resistance, 21‐24 spin filters, 16 giant magneto resistance, 25,26 magnetic sensors, 27 non‐volatile magnetic random access memories, 28,29 electro‐mechanical applications 30 . The extensive theoretical 31‐35 and experimental 36‐40 studies of the HAs have been reported in the literature in context to the thermoelectric applications due to their high power factor and low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…It opens the doors for researchers involved in spintronics. The HAs are remarkable due to their active role in the spin‐injection devices, 13‐17 spintronic devices and high thermoelectric performance, 18‐20 tunnelling magneto‐resistance, 21‐24 spin filters, 16 giant magneto resistance, 25,26 magnetic sensors, 27 non‐volatile magnetic random access memories, 28,29 electro‐mechanical applications 30 . The extensive theoretical 31‐35 and experimental 36‐40 studies of the HAs have been reported in the literature in context to the thermoelectric applications due to their high power factor and low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…After the discovery of half-metallicity in NiMnSb, this character of half-metallicity was observed in certain other group of materials [8][9][10] as well. Among different half-metallic materials Heusler alloys have drawn considerable attention because of their major role in spin-injection devices and spin filters, [11][12][13][14] giant magneto résistance, [15][16][17] spintronic and high thermoelectric performance materials, [18][19][20] electro-mechanical applications, [21] magnetic random access memories, [22,23] tunneling magneto-resistance, [24,25] etc. Heusler alloys have been examined theoretically [26][27][28][29] as well as experimentally [30][31][32][33] for use in thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, tremendous attention was also oriented towards manganese ferromagnetic Heusler, type Mn 2 YZ, (where Y = Cr, Co, Cu, Fe, Mn, Ni, Zn and Z represents the elements of group III, IV or V of the periodic table) 21,22 . Full‐Heusler alloys of type X 2 YZ crystallize in the cubic space group Fm‐3m (space group No.…”
Section: Introductionmentioning
confidence: 99%